Design of a quasi-2D rig configuration to assess nacelle aerodynamics under windmilling conditions - Boscagli, Luca; Tejero, Fernando; Swarthout, Avery E.; MacManus, David G.; Sabnis, Kshitij; Babinsky, Holger; Sheaf, Christopher T. (American Institute of Aeronautics and Astronautics (AIAA), 2023)
Aero-engine nacelles are typically designed to fulfil both design and off-design aircraft manoeuvres. Under-off design conditions one of the objective is to avoid large flow separation either on the external cowl or within the intake that can influence aircraft and engine operability. One particular scenario is represented by a low engine mass flow regime associated with one inoperative engine, also known as a windmilling condition. Under windmilling, the boundary layer on the external cowl of the nacelle can separate either due to the interaction with shockwaves or due to notable adverse pressure gradient towards the trailing edge. Both mechanisms are computationally difficult to model and there is a need for more validation of computational fluid dynamics (CFD) methods. The aim of this work is to develop a rig configuration which will provide CFD validation data for the aerodynamics of a nacelle under representative windmilling conditions. Two flight regimes are considered, namely windmilling diversion and end-of-runway. CFD simulations of a 3D nacelle are used to determine primary aerodynamic mechanisms associated with boundary layer separation. Two rig configurations are developed and both 2D and 3D CFD analyses are used to achieve the design objectives. Overall, this work presents the design philosophy and methods that were pursued to develop a quasi-2D rig configuration representative of the aerodynamics of 3D-annular aero-engine nacelles under windmilling conditions.